The Influence of Work Motivation, Leadership and Organizational Culture on Job Satisfaction in Industrial Estate in Karawang - Rismayadi, Budi; Pramudita Faddila, Syifa; Maemunah, Mumun (International Journal of Psychosocial Rehabilitation, 2020)
There are allegations that job satisfaction in Karawang Regency is influenced by work motivation, leadership, and organizational culture which is considered relatively low. The purpose of this study was to determine and analyze how the influence of work motivation, leadership, and organizational culture partially or simultaneously on employee job satisfaction in industrial area in Karawang. The population in this study amounted to 456 employees in the Industrial Estate in Karawang Regency. The research method used in this research is descriptive survey method and explanatory survey with a sample size of 372 respondents, and the data analysis method used is SEM (Structural Equation Modeling). Based on the results of the study, it was found that work motivation and organizational culture partially had a positive and significant effect on employee job satisfaction, while simultaneously these three variables were proven to have a positive and significant effect on employee job satisfaction. Partial organizational culture is the most dominant variable influencing employee job satisfaction.